PERBANDINGAN KINERJA PT SEMEN INDONESIA TBK DAN PT SEMEN BATURAJA TBK DENGAN METODE COMMON SIZE - Elga Rani Pangestu; Hari Sulistiyo (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
Companies need financial reports to assess the performance of their company's performance. The performance is assessed from the results of the financial position that occurred in a certain period. In this research, PT Semen Baturaja Tbk. and PT Semen Indonesia Tbk. become the object of research by using descriptive quantitative models through the common size method in the financial statements of each company. The results of the assessment showed a significant increase in the finances of PT Semen Baturaja Tbk. so that the company's performance is said to be good. Meanwhile, PT Semen Indonesia Tbk. even show the opposite result. The financial position of PT Semen Indonesia Tbk experienced a shock to reduce the percentage of the company's profit in 2021 due to an increase in the cost of goods sold, one of which was. In this condition, it also resulted in a decrease in the company's performance and their finances. If this continues, especially during this pandemic and economic recovery, it will further worsen the company's situation. In addition, there is an increase in coal prices which will further affect production costs.